Penyuluhan Gerakan Makan Ikan (GEMARI) untuk Mencegah Stunting di Desa Jogonegoro, Kabupaten Magelang - Avisha Fauziah Erzad; Octoriani, Widyanti; Agry, Firdausa Putra (Journal of Community Research & Engagement, 2025)
Stunting is a condition where the growth failure experienced by toddlers is caused by malnutrition that occurs since the baby is in the womb and in the early days of birth. This condition not only affects the child’s physical growth, but also cognitive development and the child’s future quality of life. The purpose of this activity is to increase community knowledge and awareness about the importance of fish comsumption as a step to prevent stunting in the Jogonegoro Village area, Magelang Regency. The method used by the service team in this activity is counseling titled the movement to eat fish (Gemari) to prevent stunting which was held on October 24, 2024, with 50 participants including lecturers, nutritionist resource persons, students, pregnant women, nursing mothers, and families who have children under five. This program adopted two educational methods in the form of direct counseling with presentations (lectures) and discussion sessions involving the participation of all participants, as well as through educational posters posted at the Jogonegoro Village Hall, Magelang District. The results of this counseling activity show that 100% of the people who attended gave a good response during the counseling and now know more about the importance of fish consumption in preventing stunting as seen from the participants post-test results.